The discourse of nation building in the Goods and Services Tax (GST) Malaysia info web portal news articles - Ong, Cheng Teik; Hajar Abdul Rahim, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This paper explores the choice of language employed by the Malaysian mainstream media to construct the former Barisan Nasional government’s role in nation building in transforming Malaysia from a developing country to a fully developed country by the year 2020 as envisioned by Vision 2020. In particular, this paper focuses on fourteen curated news articles on the GST Malaysia Info web portal set up by the former government to educate the public on the benefits of the Goods and Services Tax (GST) to the country and the people by analysing lexical words with experiential values. The data collection, categorisation and analysis entail the use of simple corpus linguistic tools and close reading of the data based on the researchers’ interpretative resources or “member’s resources” (Fairclough, 2001). The analysis of this study utilising a qualitative approach shows that the people are not only persuaded to ‘buy’ the idea of the new GST tax regime but also to buy into the ideology and discourse of nation building from the introduction of a more efficient way of tax collection. It uncovers how the manipulation of an educational campaign on the GST into a political discourse of nation building produces a positive portrayal of the government with an efficient economic development plan. Drawing on Fairclough’s (1989, 2001, 2015) three-dimensional Critical Discourse Analysis framework with a focus on different values of formal linguistic features, this study offers insights into the interplay between language, politics and nation building.